The Effect of Nutrition and Planting Media on the Productivity and Quality of Baby Kai-Lan (Brassica oleracea var. alboglabra) Cultivated Using Nutrient Film Technique System - Azmi Alvian Gabriel; Muhammad Hadziq Shafri (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The production of Brassica oleracea var. alboglabra (commonly known as baby kai-lan) with nutrient film technique can generally be performed in a relatively short period to get a high selling value of products. This study aims to determine the effect of several types of nutrients and growing media applications on the productivity and quality of baby kailan products. The research involves two test variables (nutrition and planting media) with three variations of plant nutrition and four kinds of growing media. The physical and morphological analysis results provide information on leaf width parameters. Concerning medium, perlite shows the best average yield in each plant variation. Regarding nutrients, product “Z” nutrition has the most substantial influence on the growth of the object of research. The physical and morphological tests show that the average number of leaves in almost all treatments is seven. However, the highest average number of leaves is achieved by treatments using perlite and hydroton growing media with planting nutrients “Z”. The edible weight of the harvest test shows that the treatment combination of perlite and nutrient “Z” has the highest average, i.e., 59 g per plant.